MARCSI - Inventory of Marine Citizen Science Initiatives and the FAIRness of the data they produce - Wehn, Uta; Bilbao, Ane; Somerwill, Luke; Linders, Torsten; Maso, Joan; Parkinson, Stephen; Semasingha, Christina; Woods, Sasha (IHE Delft Institute for Water Education, 2025)
Inventory (data set) of Marine Citizen Science Intiatives collected and described in the publication entitled "Past and present marine citizen science around the globe: a cumulative inventory of initiatives and data produced". AMBIO (Vol. 54, Issue 6, pp. 994–1009). https://doi.org/10.1007/s13280-024-02119-z

The metadata at SND/DORIS includes geographical coverage, but mostly only to the level of country/territory.

Inventering (dataset) av initiativ inom marin medborgarforskning insamlade och beskrivna i publikationen med titeln "Past and present marine citizen science around the globe: a cumulative inventory of initiatives and data produced". AMBIO (Vol. 54, Issue 6, pp. 994–1009). https://doi.org/10.1007/s13280-024-02119-z

Metadata på SND/DORIS inkluderar geografisk täckning, men mestadels endast till nivån land/territorium
MARCSI - Inventory of Marine Citizen Science Initiatives and the FAIRness of the data they produce
MARCSI
Keywords: citizen science; Habitats and biotopes; Naturtyper och biotoper; Oceanographic geographical features; Geografiska oceanografiska förhållanden; Sea regions; Havsområden; Species distribution; Arters utbredning; open data; öppen data; marine pollution; marina föroreningar; FAIR; FAIR; marine monitoring; marin övervakning; marine biology; marin biologi; Environmental Sciences; Miljövetenskap; Ecology; Ekologi; Other Social Sciences; Annan samhällsvetenskap; Biota; Biologi och ekologi; Oceans; Kust och hav